Detection and molecular characterization of mastadenoviruses in calves with respiratory system infection - İlke Karayel Hacıoğlu; Selda Duran Yelken; Feray Alkan (Eurasian Journal of Veterinary Sciences)
Aim: Bovine adenovirus (BAdV) is one of the viral agents that causes respiratory illness in cattle, along with numerous other viral agents. Although the prevalence of BAdV has been determined by serological studies conducted in our country, there are limited data on the detection of BAdVs in respiratory system samples, and there is no study on their molecular characterization. The aim of this study was to detect and characterize BAdVs of the Mastadenovirus genus. Materials and Methods: In this study, a total of 64 nasal swabs and one lung sample from 65 cattle of different ages with respiratory system disease symptoms were used. After the extraction of viral DNA, they were tested by PCR using primers targeting the hexon gene region and the expected size of amplicons were sequenced. Results: According to the PCR results, three samples were found positive and the positivity rate was detected as 4.6%. Out of positive samples, two were able to be sequenced and one clustered in the BAdV-2 serotype while the other was grouped in the BAdV-3 serotype. Conclusion: In this study, it was revealed that BAdVs are contributing agents in respiratory system infection in our country. Also, this is the first study reporting the molecular characterization of BAdV-2 and BAdV-3 in calves with respiratory system infection in Turkey.